Effect of temperature and drying time on physicochemical of beetroot (Beta vulgaris L. var. Rubra L.) flour - Prabowo, Ulya Sarofa; Aprilia, Rina (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2022)
Beetroot is a food source that is rich in nutrient value, including carbohydrates, minerals, vitamin C and betalains as a source of antioxidants. The high-water content causes the beetroot to be easily damaged, therefore a suitable method, is needed to preserve it. Like being processed into intermediate goods such as flour. The aim of this research was to determine the effect of temperature and drying time on the chemical characteristics and color of beetroot flour. This research used a completely randomized design (CRD) in factorial with two factors, namely the drying temperature range (50 °C, 60 °C, and 70 °C) and the drying time range (6, 7, and 8 hours). ANOVA and DMRT advanced test were used to test the resulting data. The results showed that the best treatment was obtained from sample treated a drying temperature of 50oC and a drying time of 6 hours, the yield value was 13.53%, with water content of 12.61%, ash 2.65%, fat 0.73%, protein 11, 16%, carbohydrate 72.85%, antioxidant activity 69.80%, anthocyanin 69.81 mg.100 g–1, Vitamin C 31.92 mg.100 g–1, color intensity L* 15,825, a* 7.82, b* 2.78.